Post-Political Governance and the Return of the Political: PROPER-rated Geothermal Enterprise, Environmental Problems, and Civil Resistance in Dieng Plateau, Central Java - Wiguna, Bangkit Adhi; Fiko, Gloria Evanda (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2024)
The Industrial Environmental Rating Program (PROPER) from the Ministry of Environment and Forestry of the Republic of Indonesia has produced various outcomes. Many companies strive to meet the PROPER assessment criteria, earning ratings represented by colors ranging from black to gold. Unfortunately, the indicators set by PROPER, namely compliance and beyond-compliance assessment criteria, are limited to technical and managerial aspects rather than substantial ones. Consequently, the ratings often become a means for environmentally polluting companies to polish their public image and attract investment. PT Geo Dipa Energi (Persero), a state-owned geothermal enterprise, is one of many companies that have obtained a blue PROPER rating. This company's presence in Dieng, Central Java, has faced civil resistance due to the various pollution issues caused by their activities. The company uses the blue PROPER rating label to create a mechanism called “post-political governance” to discipline civil resistance. This mechanism refers to the process of repressing the political dimension in society by introducing apolitical mechanisms. These apolitical mechanisms are found in the values of good governance, such as participation, transparency, fairness, accountability, and public inclusion, which PROPER aims to implement. This research was conducted in Karang Tengah Village, Dieng, and remotely from different locations. The findings show that Dieng residents, whose political dimension is being disciplined, are able to reclaim their political agency through civil and discursive political resistance—a set of conditions that Wilson and Swyngedouw refer to as “the return of the political.” This research aims to present a critical perspective on Corporate Social Responsibility (CSR) practices by companies within the framework of PROPER, while also highlighting the role of the community as key actors in challenging the discourse of empowerment constructed by the company and PROPER policy.